2017
DOI: 10.3813/aaa.919128
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Delaminations in Composite Structures Using a Baseline-Free, Sparse Array Imaging Technique Based on Nonlinear Lamb Wave Propagation

Abstract: Environmental factors such as temperature and humidity influence the efficacyo fd efect imaging procedures based on the identification of changes between an intact state and the current state of as ample/component/structure in the presence of ad efect. In this paper,w ef ocus on the Reconstruction Algorithm for Probabilistic Inspection of Damage (RAPID)a nd propose an onlinear Lamb wave version of RAPID to visualize a delamination in acomposite structure without having to knowanything about the intact state, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…The result of the experiment showed that damage detection and localization is possible with the RAPID algorithm. Since the correlation coefficient is sensitive to frequency changes or flight time variations 25 and SAPS focus on amplitude changes, the fusion combining multiple indicators could be considered. However, some limitations still exist for the basic RAPID-Algorithm due to peak intensity at the intersection points.…”
Section: Resultsmentioning
confidence: 99%
“…The result of the experiment showed that damage detection and localization is possible with the RAPID algorithm. Since the correlation coefficient is sensitive to frequency changes or flight time variations 25 and SAPS focus on amplitude changes, the fusion combining multiple indicators could be considered. However, some limitations still exist for the basic RAPID-Algorithm due to peak intensity at the intersection points.…”
Section: Resultsmentioning
confidence: 99%
“…The damaged index selected is the Subtraction Scaling Method (SSM) [23], which normalizes the compared signals and calculates the area between them (Figure 10) through integration, in the analyzed time section nT of the signal (7).…”
Section: Imaging Algorithmmentioning
confidence: 99%
“…An alternative to the traditional procedure of damage detection (i.e., baseline vs. damaged) is the evaluation comparing two tests in the damaged state conditions (baseline-free), but varying some conditions of the excitation (amplitude of the excitation signal [23], multi-frequency tests [24], etc.). However, since this methodology is based on the appearance of nonlinearities in the structure response (e.g., non-uniform signal's envelope distribution variation, appearance of higher-order harmonics or changes in phase velocity), the possible inherent nonlinearities of the composite material make the application of this method not suitable to all geometries (e.g., the geometry generates itself nonlinearities in the guided waves).…”
Section: Introductionmentioning
confidence: 99%
“…One way for identifying the Lamb wave modes that are propagating in the sample is by using 2D FFT. 34 2D FFT graphs are obtained by measuring the wave signal along a straight line as shown in Figure 4. In Figure 4, 64 signals are measured along a straight line on the left side of the hole for calculating the 2D FFT.…”
Section: Finite Element Modelmentioning
confidence: 99%